2015
DOI: 10.1371/journal.pone.0134592
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genomic Diversity among Bovine-Adapted Staphylococcus aureus: Evidence for a Genomic Rearrangement within CC97

Abstract: Staphylococcus aureus is an important pathogen associated with both human and veterinary disease and is a common cause of bovine mastitis. Genomic heterogeneity exists between S. aureus strains and has been implicated in the adaptation of specific strains to colonise particular mammalian hosts. Knowledge of the factors required for host specificity and virulence is important for understanding the pathogenesis and management of S. aureus mastitis. In this study, a panel of mastitis-associated S. aureus isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 56 publications
(60 reference statements)
4
59
0
Order By: Relevance
“…CC1 is a common lineage among humans including both MSSA and community-acquired (CA-) MRSA; and CC1 is also frequently found in cattle [114,115]. A strain that closely resembled the MRSA from rooks was frequently found among humans in Romania [116].…”
Section: Resultsmentioning
confidence: 99%
“…CC1 is a common lineage among humans including both MSSA and community-acquired (CA-) MRSA; and CC1 is also frequently found in cattle [114,115]. A strain that closely resembled the MRSA from rooks was frequently found among humans in Romania [116].…”
Section: Resultsmentioning
confidence: 99%
“…Both sequence types have been reported extensively from bovine mastitis cases in many countries including, but not limited to, Brazil, Chile, Italy, Japan, Norway, Spain, the Netherlands and the United States (Smith et al, 2005; Rabello et al, 2007; Hata et al, 2010). The expansive distribution of this successful lineage suggests that the strains are specifically adapted to the bovine host (Smith et al, 2005; Budd et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have suggested that a few specialized S. aureus strains are responsible for the majority of bovine intramammary infections (IMIs) worldwide (Kapur et al, 1995; Zadoks et al, 2002; Sakwinska et al, 2011; Budd et al, 2015). However, the occurrence of herd-specific strains has also been reported (Joo et al, 2001; Sommerhäuser et al, 2003; Rabello et al, 2007; Oliveira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Within each of the major bovine IMI pathogen species, a diversity of strains and lineages (see Table 1) exists, each with a potentially unique repertoire of virulence factors and immune-stimulatory antigens (Budd et al, 2015;Hossain et al, 2015;Keane, 2016). Strain typing of E. coli, Strep.…”
Section: Genomics Of Imi Pathogensmentioning
confidence: 99%
“…uberis considered environmental pathogens (Bradley, 2002). More recently it has been recognized that some IMI pathogens may be capable of both contagious and environmental transmission and that the mode of transmission may be associated with the strain rather than species of pathogen (Zadoks et al, 2000;Budd et al, 2015;Davies et al, 2016). Prevention and management of contagious mastitis relies on the implementation of several well-characterized infection control strategies such as those outlined in the National Mastitis Council's "5-point" plan (NMC, 2011), later extended to a "10-point" plan.…”
Section: Introductionmentioning
confidence: 99%